Analysis of problems of regulatory and technical support of organic production in Ukraine - Бубела, Тетяна Зіновіївна; Воробець, Ольга Володимирівна (Technology audit and production reserves, 2014)
It is analyzed a state of organic production in Ukraine in comparison with foreign experience. A sociological study of demand for organic products in the population of Western Ukraine is conducted. It is described the trends and characteristics of organic production of agricultural products in Ukraine and in Europe, prompted a number of policy measures on the formation of organic conducting of agricultural activities in Ukraine. In particular, such measures may include the need to improve the national framework of regulations relating to the industry, because domestic organic control system needs substantial reforms, which should be based on the experience of developed countries. So when will have clearly defined rules and standards of production and marketing of organic products then will be fully realized Ukrainian right on health safety. In fact, eating organic production may be significant strengths in Ukraine, the direction, moving on which we can stand tall on the world market and to enable the development of not only agriculture, but also many other related industries.